Message - Islam, Dr. Md. Shahidul (Universal Journal of Pharmaceutical Research, 2021)
Human stay alive on knowledge and scientific knowledge does not cease to go forward. Scientific Research and development at this instant are obligatory functions of teaching. The academic as well as research worth inherent in it is so exponential. The platform of UJPR is so much intended to persuade all the involved in the journal to contribute in assembly of the expertise, knowledge as well as wisdom. It inserts to verve of what are exiting on in lectures, practical sessions, seminar classes, library works and study, tutorials as well as research hours. UJPR is an universal journal that congregates academic professionals, editors and researchers from the globe. The scientific papers restrained in current issue are very important, informative, and instructive and also has been reviewed through several phases to uphold the quality of paper and rigorously follow public ethics (ICJME). Editorial Board members instigates from many countries like; India, Bangladesh China, Egypt, Nigeria, Malaysia, Ireland, Indonesia, Hungary, United States, Switzerland, Italy, Spain, Saudi Arabia, Syria, United Kingdom, South Africa, Iraq, and Brazil. So National as well as International Editorial board members are very much dynamic for valued guidance, scientific suggestions, encouragement, continuous monitoring and contribution. Authors prompt from Nigeria, Egypt, India, China, and many others. The citation of UJPR is very much superior. It is indexed and abstracted in more than 40 well known indexing services including CAS, CASSI (American Chemical Society), DRJI, BASE, Directory of Science, ROAD, ESJI, COSMOS, Academic Keys, etc. many more. It is my great honor to inform you that in prior years "Universal Journal of Pharmaceutical Research" have successfully published more than 200 articles from many countries including Nigeria, Yemen, India, Cameroon, Egypt, China, Pakistan, Iran, Iraq, Malaysia, Sudan, Bangladesh, Saudi Arabia, USA, West Indies, and Nepal. The overwhelming yield of such a ample affluent portfolio of learned as well as glowing researched papers will absolutely be of much promote of the boarder arena of the world. Greetings all the researchers for their precious contribution in this issue and most welcome the younger and prominent researcher for the upcoming issue.